Élisabeth Vonarburg et la Science-Fiction québécoise: une approche originale - De Luca, Ylenia (Ponti/Ponts, 2022)
Today, we can say that the earliest examples of science fiction (SF) writing in Europe date back to the 17th century. The term “science-fiction” was invented in the United States by Hugo Gernsback in 1926 to distinguish his magazine Amazing Stories, in which he attributed the term to authors such as Poe, Verne and Wells, from other magazines such as Weird Tales. In Québec, it was not until 1968 that Darko Suvin, who would co-found the journal Science Fiction Studies with R.D. Mullen in 1973, gave an early version of his definition of SF during a conference at Yale University. Élisabeth Vonarburg, who is of French descent and emigrated to Québec after earning a degree in Lettres modernes in France, has been one of the most influential voices in Québec SF since 1974. With her articles in Solaris, a magazine she edited, her writing courses, and the controversies she has stirred up, she constitutes an important reference point for Quebecers and for all Francophone SF in general. Additionally, Élisabeth Vonarburg is, together with Esther Rochon, one of the few female francophone writers to compete with the great female American SF writers, such as Ursula Le Guin. This is a real revolution in the field of Québec SF due to the fact that, in general, a non-English-speaking SF author becomes world famous only if he or she is translated and published in English, then consecrated by American awards. Almost every publication by this writer has won several awards: “Le Grand Prix de la SF française” in 1982, and the Special Jury Prize at the Philip K. Dick Award in 1993, for the U.S. translation of Chroniques du pays des mères. In this essay, I will, therefore, first inquire about SF and its specificity in Québec, and then address the originality of Vorarburg in the Québec context.